Dendritic cell-derived MYD88 potentiates as a biomarker for immune regulation in hepatocellular carcinoma and may predict a better immunological result - Liu, Zheming; Zhu, Hengbo; Zhang, Fengxia; Huang, Wenting; Zhu, Shipeng; He, Songjiang; Yao, Yi; Song, Qibin; Zhang, Xue (Frontiers in Cell and Developmental Biology, 2025)
IntroductionMYD88 (myeloid differentiation primary response 88) is a key adaptor protein mediate immune responses, primarily through Toll-like receptors (TLRs) and interleukin-1 receptor (IL-1R) signaling. The TLR/MYD88 pathway plays a critical role in dendritic cells (DC) maturation and function, contributing to the body’s innate immunity. Recent studies have further highlighted MYD88’s pivotal role in intrinsic immunity and its regulatory influence on the tumor microenvironment (TME) in hepatocellular carcinoma (HCC). The expression of MYD88 in DCs and its regulatory role in the TME have gained increasing attention.MethodsRNA-sequencing data retrieved from the TCGA and GEO databases were utilized for both the training and validation of our signature. Single-cell RNA transcriptome data from GEO were analyzed to investigate the correlation among subclusters of T cells, myeloid cells, and dendritic cells (DCs) within the HCC tumor microenvironment (TME). A combination of bioinformatics and machine learning approaches was employed to perform statistical analyses.Additionally, flow cytometry was conducted to quantify T cell subtypes and assess biomarker expression in DCs. A BALB/c-derived xenograft mouse model was established to evaluate the functional role of MyD88 in tumor progression and immunotherapy response. Furthermore, immunohistochemical (IHC) staining was performed to reassess the biological effects of MyD88 in HCC patients undergoing immune checkpoint inhibitor (ICI) therapy.ResultsOur pan-cancer data analysis further highlights the significant impact of MYD88 on clinical outcomes in HCC. Analysis of TCGA and GEO databases confirms that MYD88 serves as a key signaling molecule in DCs, reinforcing its critical role in immune regulation. Our in vitro experiments demonstrates that MyD88 modulates T cell function through DCs. In vivo, H22 tumor cells exhibited accelerated growth in MyD88 knockout mice and a reduced response to anti-PD-1 treatment, whereas wild-type mice showed the opposite trend.DiscussionThese findings underscore the critical role of MYD88 in DC function, suggesting its potential as a biomarker for immunoregulation in HCC. By shaping the TME, MYD88 not only regulates the immune response in HCC but also influences patient clinical outcomes. Both ex vivo and in vivo experiments further validate that MYD88 impacts DC functionality, contributing to variations in HCC progression